Ankle Fractures in Diabetic Patients: A Critical Analysis. Issue 3 (16th March 2023) - Goldberg, Ellen M.; Polachek, William S.; Hynes, Kelly
Abstract : » Patients with diabetes are at higher risk for complications after surgical fixation of unstable fractures due to impaired neurovascular functioning and wound-healing capabilities. » Patients with uncontrolled diabetes have higher rates of complications when compared with patients with controlled diabetes. » Despite higher rates of complications, operative fixation of unstable ankle fractures in diabetic patients reliably leads to a functional lower extremity with an overall lower rate of complications than nonoperative management. » Operatively and nonoperatively managed ankle fractures in patients with diabetes should remain non–weight-bearing for an extended period of time. » Discussion of risk of poor outcomes including deep infection, loss of reduction, return to the operating room, and risk of arthrodesis or amputation should be explicitly discussed with patients and families when managing unstable ankle fractures in diabetic patients.